Novel Tetraphenolic Porphyrazine Capable of MRSA Photoeradication - Wojciech Szczolko; Eunice Zuchowska; Tomasz Koczorowski; Michal Kryjewski; Jolanta Dlugaszewska; Dariusz T. Mlynarczyk (Molecules)
This work presents the synthesis, characterization and evaluation of physicochemical and biological properties of two new aminoporphyrazine derivatives bearing magnesium(II) cations in their cores and peripheral pyrrolyl groups. The synthesis was carried out in several stages, using classical methods and the Microwave-Assisted Organic Synthesis (MAOS) approach. The obtained compounds were characterized using spectral techniques: UV-Vis spectrophotometry, mass spectrometry, 1H and 13C NMR spectroscopy. The porphyrazine derivatives were tested for their electrochemical properties (CV and DPV), which revealed four redox processes, of which in compound 7 positive shifts of oxidation potentials were observed, resulting from the presence of free phenolic hydroxyl groups. In spectroelectrochemical measurements, changes in UV-Vis spectra associated with the formation of positive-charged states were noted. Photophysical studies revealed the presence of characteristic absorption Q and Soret bands, low fluorescence quantum yields and small Stokes shifts. The efficiency of singlet oxygen generation (ΦΔ) was higher for compound 6 (up to 0.06), but compound 7, despite its lower efficiency (0.02), was distinguished by a better biological activity profile. Toxicity tests using the Aliivibrio fischeri bacteria indicated the lower toxicity of 7 compared to 6. The most promising result was the strong photodynamic activity of porphyrazine 7 against the Methicillin-resistant Stapylococcus aureus (MRSA) strain, leading to a more-than-5.6-log decrease in viable counts after the colony forming units (CFU) after light irradiation. Compound 6 did not show any significant antibacterial activity. The obtained data indicate that porphyrazine 7 is a promising candidate for applications in photodynamic therapy of bacterial infections.